Pemanfaatan Kesenian Music Islam (Nasyid) sebagai Strategi Inovatif dalam Pembelajaran PAI - Muhammad Rizky Akbar; Intania Gunasah; Maharani Maharani; Muhajir A.M Al Raaji; Abdul Azis (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The use of Islamic music, especially nasyid, as a creative learning strategy in Islamic Religious Education (PAI) plays an important role in increasing students' motivation, understanding, and appreciation of religious values. This study uses a qualitative descriptive method to describe in depth how nasyid can be used as an innovative and effective learning medium to enrich the IRE teaching process. The findings show that the application of nasyid in the teaching and learning process can create a more interesting, interactive, and enjoyable learning atmosphere. This condition has been proven to encourage active student participation, making learning activities more meaningful and memorable. In addition, nasyid effectively helps students improve their memory and ability to memorize religious material in an easier and more enjoyable way. The positive impact is not only seen in cognitive aspects but also in the overall formation of students' religious character. Through nasyid, moral and spiritual values can be instilled more deeply, naturally, and continuously in everyday life. However, this study also found several obstacles, such as limited supporting facilities and the need to develop teachers' competencies in optimally applying nasyid as a learning medium. Therefore, the use of nasyid in PAI learning can be seen as a strategic innovation that has the potential to improve the quality of religious education holistically and have a positive impact on the development of students in a dynamic and challenging modern era.